Accuracy of pSOFA Score in Predicting Outcomes in Critically Ill Children - Zamir, Saba; Nadeem, Muhammad Tariq; Tabussam, Samina (Pakistan Armed Forces Medical Journal, 2023)
Objectives: To determine the diagnostic accuracy of the pSOFA score in predicting mortality in critically ill pediatric patients. Study Design: Cross-sectional validation study. Place and Duration of Study: Department of Paediatrics, Pak-Emirates Military Hospital, Rawalpindi Pakistan, Aug 2021 to Feb 2022. Methodology: We studied 76 critically ill paediatric patients. All patients underwent pSOFA scoring on admission and then at 72 hours post-admission and were followed up till discharge or till mortality occurred. A pSOFA score of >10 was considered a high mortality risk. The two-by-two table was constructed to calculate the sensitivity, specificity and diagnostic accuracy of the pSOFA score in predicting the occurrence of death. Results: The pSOFA score had a sensitivity of 88.9% at Day-0, which improved to 100% by Day-7 in predicting whether mortality occurred. The specificity was 80.6% on Day-0 and 97.0% on Day-7. The diagnostic accuracy of pSOFA in predicting mortality was 81.6% when performed on the day of admission, which increased to 90.8% when calculated on Day 3 and was the highest on Day-7 when it was 97.4%. Conclusion: The pSOFA score has good diagnostic accuracy in predicting the occurrence of mortality in paediatric patients admitted to intensive care, which increases as the length of stay increases.